Seed-borne mycoflora of Niger (Guizotia abyssinica Cass.) and its effect on germination - M. KRISHNAPPA*, O. NAGARAJA and (Indian Phytopathology, 2009)
Niger (Guizotia abyssinica Cass.) seeds were analyzed for mycoflora. Thirty two species belonging to six genera were isolated from 126 Niger seed samples collected from the field (9), farmers (59), retail shops (22) and APMC markets (36) of Karnataka during kharif 2005. Seeds were subjected for seed health test by SBM, PDA, WA and 2,4-D methods. Farmers and field samples shows higher incidence of pathogens than others. The associated fungi decreased the germination. Some important fungal species are Alternaria alternata, Fusarium oxysporum, Alternaria sp., Sclerotinia sclerotiorum, Verticillium dahliae, Chaetomium globosum, Chaetomium sp., Oedocephallum caprophyllum, Gliocladium virens, Haplosporangium sp., Phoma glomerata, Cladosporium cladosporioidis, C. chlorocephallum, Myrothecium roridum, Cunninghamella elegans, Cladosporium sp., Stachybotrys atra, Acremonium spp., Aspergillus flavus, A. niger, A. ochraceus, A. candidus, A. terreus, A. versicolor, Penicillium digitatum, Penicillium sp., Nigrospora sp., Trichoderma harzianum, T. viride, Rhizopus stolonifer and R. nigricans. Among the samples screened, Bangalore rural district samples showed higher incidence of Alternaria alternata 46%, Fusarium oxysporum 40%, Alternaria sp. 28%, Aspergillus flavus 21% and Haveri district sample showed less incidence of pathogenic fungi. Among the seed health tested methods, standard blotter method proved superior over the other methods. These pathogenic and saprophytic fungi were isolated from normal, abnormal, un germinated and rotted seeds.